International practices in the dietary management of fructose 1-6 biphosphatase deficiency - A. Pinto; M. Alfadhel; R. Akroyd; Y. Atik Altınok; S. M. Bernabei; L. Bernstein; G. Bruni; G. Caine; E. Cameron; R. Carruthers; B. Cochrane; A. Daly; et al. (Orphanet Journal of Rare Diseases, 2018)
Abstract Background In fructose 1,6 bisphosphatase (FBPase) deficiency, management aims to prevent hypoglycaemia and lactic acidosis by avoiding prolonged fasting, particularly during febrile illness. Although the need for an emergency regimen to avoid metabolic decompensation is well established at times of illness, there is uncertainty about the need for other dietary management strategies such as sucrose or fructose restriction. We assessed international differences in the dietary management of FBPase deficiency. Methods A cross-sectional questionnaire (13 questions) was emailed to all members of the Society for the Study of Inborn Errors of Metabolism (SSIEM) and a wide database of inherited metabolic disorder dietitians. Results Thirty-six centres reported the dietary prescriptions of 126 patients with FBPase deficiency. Patients’ age at questionnaire completion was: 1-10y, 46% (n = 58), 11-16y, 21% (n = 27), and >16y, 33% (n = 41). Diagnostic age was: <1y, 36% (n = 46); 1-10y, 59% (n = 74); 11-16y, 3% (n = 4); and >16y, 2% (n = 2). Seventy-five per cent of centres advocated dietary restrictions. This included restriction of: high sucrose foods only (n = 7 centres, 19%); fruit and sugary foods (n = 4, 11%); fruit, vegetables and sugary foods (n = 13, 36%). Twenty-five per cent of centres (n = 9), advised no dietary restrictions when patients were well. A higher percentage of patients aged >16y rather than ≤16y were prescribed dietary restrictions: patients aged 1-10y, 67% (n = 39/58), 11-16y, 63% (n = 17/27) and >16y, 85% (n = 35/41). Patients classified as having a normal fasting tolerance increased with age from 30% in 1-10y, to 36% in 11-16y, and 58% in >16y, but it was unclear if fasting tolerance was biochemically proven. Twenty centres (56%) routinely prescribed uncooked cornstarch (UCCS) to limit overnight fasting in 47 patients regardless of their actual fasting tolerance (37%). All centres advocated an emergency regimen mainly based on glucose polymer for illness management. Conclusions Although all patients were prescribed an emergency regimen for illness, use of sucrose and fructose restricted diets with UCCS supplementation varied widely. Restrictions did not relax with age. International guidelines are necessary to help direct future dietary management of FBPase deficiency.